Asymmetric synthesis of (R)-hexane-1,5-diol and (R)-hex-3-ene-1,5-diol via a tandem asymmetric conjugate addition stereospecific Meisenheimer rearrangement protocol - Davies, S; Smyth, G (1996)
Stereoselective conjugate addition of (R)-lithium N,α-dimethylbenzylamide to tert-butyl (E,E)-hexa-2,4-dienoate, followed by reduction of the ester to the corresponding alcohol, affords a substrate which undergoes, on oxidation, a stereospecific Meisenheimer rearrangement to give a single diastereomer of the corresponding trialkylhydroxylamine. Cleavage of the N-O bond gives (R)-hex-3-ene-1,5-diol and subsequent hydrogenation of the double bond affords (R)-hexane-1,5-diol in high e.e.